A Novel FM-DCSK Secure Communication System - Gang Zhang; Yuan Wang; Ying Wang (Dianxin kexue)
The bit energy of chaotic signals in DCSK system is not stable,which will cause the estimation interference and the bit error rate decline. At the same time, the system's transmission rate is lower and the security is poorer compared with other system. In order to solve these problems, a novel FM-DCSK secure communication system was proposed which was combined the FM modulation with the modified DCSK system.The bit energy of signals remained stable by using FM modulation so that the BER performance in such system can be improved. Meanwhile, the system was also combined with the modified DCSK system which uses two-channel scheme, therefore it can improve the transmission efficiency and further improve the security performance. Finally, the theoretical analysis and the simulation results prove that the relative performance in this proposed system can be greatly improved.